Analysis on “three-box” model of stress-strain in frozen soil porous media based on representative macroscopic Volume - Han, Qiang; Wang, Zhiguo; Teng, Zhenchao; Zhang, Yunfeng; Cao, Jing (Frontiers in Earth Science, 2022)
In cold regions, the pore space's composition and phase state can affect the elastic modulus of the media. During the winter, the freezing conditions in the soil results in the release of water from the pore space, which results in significant changes in the media's distribution and composition. There are a few weaknesses in the current research with respect to the elastic modulus change example of frozen soil. This paper presents that the Representative Macroscopic Volume (RMV) choice strategy is provided for frozen soil with porosity as a typical condition variable. Under the state of freezing, a "three-box" analytical model for stress-strain calculation of frozen soil porous media is established, namely, the black-box model, the gray-box model, and the white-box model. The relevant equations for calculating elastic modulus are presented based on the proposed "three-box" model and the analysis of the stress conduction process. Results show that the discrepancy between the computed and experimental values of the white-box model is slight, and the elastic modulus of frozen soil calculated by the model established in this paper is consistent with the actual state. It can be deduced that the model established in this paper has practicality and the conclusions of the study are of guiding significance for the application of frozen soil.